2014
DOI: 10.5539/ass.v10n12p98
|View full text |Cite
|
Sign up to set email alerts
|

Audit Committee Characteristics and Executive Committee Characteristics and Firm Performance in Oman: Empirical Study

Abstract: This study attempted to examine the association between two important committees of corporate governance practice namely, audit committee characteristics and executive committee characteristics, and firm performance. The data used comprised of non-financial companies listed in Muscat Security Market (MSM) through 2011 and 2012. Based on widely existing literature that studied the relationship between corporate governance and firm performance, studies that investigated the role of executive committee with firm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The larger audit committee will increase the number of meetings and result in more effective oversight (Raghunandan et al, 2001). Although Wei (2007), Al Matari et al (2014), andOradi et al (2017) did not find any evidence of a significant association between the audit committee size and the company performance; the outcomes of Al-Mamun et al (2014) and Reddy et al (2010) witnessed that the audit committee size positively affects the firm performance. Furthermore, Rezaei and Abbasi (2015) showed that the audit committee size of Iranian firms affects corporate performance.…”
Section: The Theoretical Issues Hypothesis Development and Literaturementioning
confidence: 98%
“…The larger audit committee will increase the number of meetings and result in more effective oversight (Raghunandan et al, 2001). Although Wei (2007), Al Matari et al (2014), andOradi et al (2017) did not find any evidence of a significant association between the audit committee size and the company performance; the outcomes of Al-Mamun et al (2014) and Reddy et al (2010) witnessed that the audit committee size positively affects the firm performance. Furthermore, Rezaei and Abbasi (2015) showed that the audit committee size of Iranian firms affects corporate performance.…”
Section: The Theoretical Issues Hypothesis Development and Literaturementioning
confidence: 98%
“…There are a variety of reliable standards and criteria that can be used to measure corporate value, the first group is accounting standards which depend on the accounting and financial information derived from the corporate financial statements, and include ROA, EPS, and interest coverage ratio, while the second group is economic measures, such as added value measurements, and the third group deals with the market standards and includes measurements like Tobin Q ratio, and the ratio of market value to book value. Accounting standards represented in ROA method consider one of the most used criteria to measure the corporate value in accounting (Al-Matari, et al, 2014;Afza & Nazir, 2014;Al-Karasneh & Bataineh, 2018).…”
Section: Corporate Valuementioning
confidence: 99%
“…In many instances, earnings quality misinform users of financial statements through provision of incorrect information on company's financial performance or state (Iturriaga & Hoffmann, 2005). Therefore, a larger audit committee may be key to constraining the occurrence of earnings management (Al Matari et al, 2014;Rezaei & Abbasi 2015;Abdul Rahman & Heneem, 2006;Oradi et al, 2017). Contrarily, studies of Yang and Krishnan (2005); Hillman and Dalziel (2003) indicate existence of a negative and significant relationship between audit committee size with earnings quality.…”
Section: Audit Committee and Earnings Qualitymentioning
confidence: 99%